Multifaceted Interaction Between Hepatitis B Virus Infection and Lipid Metabolism in Hepatocytes: A Potential Target of Antiviral Therapy for Chronic Hepatitis B - Zhang, Jiaxuan; Ling, Ning; Lei, Yu; Peng, Mingli; Hu, Peng; Chen, Min (Frontiers in Microbiology, 2021)
Hepatitis B virus (HBV) is considered a "metabolic virus" and affects many hepatic metabolisms. However, how HBV affects lipid metabolism in hepatocytes remains uncertain yet. Accumulating clinical studies suggested that chronic HBV infection was associated with lower levels of serum total cholesterol and triglycerides and a lower prevalence of hepatic steatosis. And this relationship could be adjusted by some metabolic and clinical parameters of patients with chronic hepatitis B. Furthermore, mechanisms of how HBV infection affected liver lipid metabolism had also been explored in amounts of studies based on cell lines and mice models. These results demonstrated that HBV replication or HBx protein could not only activate some critical enzymes in the pathway of lipid synthesis, such as fatty acid synthase and sterol-regulatory element-binding protein 1c and 2, but also upregulate several lipolysis pathways, including fatty acid oxidation and bile acid synthesis.Thus, HBV infection induced extensive and diverse changes in hepatic lipid metabolism, by increasing both hepatic lipogenesis and lipid catabolism.Moreover, increasing studies investigated effects on HBV replication by inhibiting or enhancing certain lipid metabolism-related protein or product, and found some potential targets to inhibit HBV replication or expression. Therefore, in this article, we intend to comprehensively review these publications and clue the connection between clinical observations and experimental findings to beter understand the interaction between hepatic lipid metabolism and HBV infection. Nevertheless, these evidences are far from conclusive, and there is still a long way to go before clarifying the complex interaction between hepatic lipid metabolism and HBV infection.